A new Late Cretaceous leaf mine Leucopteropsa spiralae gen. et sp. nov. (Lepidoptera: Lyonetiidae) represents the first confirmed fossil evidence of the Cemiostominae. (5th February 2021) - Maccracken, S. Augusta; Sohn, Jae-Cheon; Miller, Ian M.; Labandeira, Conrad C.
Abstract : A new fossil leaf mine ichnogenus and species, Leucopteropsa spiralae gen. et sp. nov. (Lepidoptera: Lyonetiidae), from the Upper Cretaceous Kaiparowits Formation (Campanian age, c. 76.6 to 74.5 Ma) in Utah, USA, is the earliest record (75.6 ± 0.18 Ma) and only fossil evidence of a lyonetiid-like leaf-mining moth, as well as one of the oldest known fossils within the Yponomeutoidea-Gracillarioidea clade. The blotch-style mine consists of a central oviposition, or egg laying, site with a spiral trail packed with faecal pellets that concentrically spirals outwards. The trail increases in width from oviposition site to terminus, the trajectory of the trail does not cross itself, and there is no apparent pupation chamber present. The morphology of the fossil mine is reliably associated with Cemiostominae and is most similar to mines produced by extant members of the genus Leucoptera, such as the mountain ash bent-wing moth, Leucoptera malifoliella, and the laburnum leaf miner L. laburnella . The leaf-mining moth responsible for L. spiralae may be an early member of the genus Leucoptera or other Cemiostominae genera, and the new ichnogenus Leucopteropsa is erected because the morphology, and therefore the taxonomy, of the moth specifically responsible for L. spiralae mines was not preserved in association with the leaf mine. Despite the phylogenetic analysis of 15 lyonetiids undertaken in this study and the need for further phylogenetic work for the Lepidoptera, particularly the placement of the family Lyonetiidae and the subfamily Cemiostominae within the larger Yponomeutoidea-Gracillarioidea phylogeny, this fossil provides an important Late Cretaceous (∼76 Ma) calibration point for lepidopteran phylogeny and serves as an indicator for the antiquity of the most diverse lepidopteran group, Ditrysia. Because lepidopteran body fossils are extremely rare, owing to their small and lightly sclerotized bodies, this discovery also underscores the importance of ichnofossils in the lepidopteran fossil record. http://zoobank.org/urn:lsid:zoobank.org:pub:52B20B15-5C1A-4916-9096-A490DFED7D1C